Effects of the Molecular Design on the Supramolecular Organization of Luminescent Pt(II) Complexes. Issue 10 (10th July 2019) - Aliprandi, Alessandro; Capaldo, Luca; Bobica, Carla; Silvestrini, Simone; De Cola, Luisa
Abstract: Self‐assembly is an extremely important processes that allows the constructions of large supramolecular architectures through encoded information present in the components. A subtle change in the chemical structure of the single unit can dramatically change the kinetics and thermodynamic pathway. We demonstrate that a minor change, introduced by designing the structure of a family of Pt(II) complexes can influence the color of the emission of the assemblies and their kinetic behaviour. The assembly processes, visualized by confocal microscopy, and detailed through photophysical measurements, reveal that the establishment of intermolecular interactions, as well as electronic factors lead to completely different assemblies in solution of the platinum compounds. A correlation between the observed behaviour and the chemical structure of the compounds is discussed and the results indicate a strong kinetic control of the supramolecular processes. Abstract :